2017
DOI: 10.5858/arpa.2016-0441-oa
|View full text |Cite
|
Sign up to set email alerts
|

Commutability of Reference Materials for α-Fetoprotein in Human Serum

Abstract: - Our results suggested that the Beijing Center for Clinical Laboratories and Beijing Controls and Standards Biotechnology materials were commutable across all 5 instrument platforms, whereas the Bio-Rad quality controls were limited by the concentration of AFP and the instrument platforms used. Caution needs to be taken in using water to dilute the World Health Organization 72/225 reference material because its commutability is limited to high concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In this study, we also described a method of harmonization using non-commutable EQA materials, which is important for EQA organization. Although we could not demonstrate the commutability of human serum pools (commutable EQA), some studies have provided evidence regarding the commutability of these materials through the same preparation technique [ 12 , 14 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this study, we also described a method of harmonization using non-commutable EQA materials, which is important for EQA organization. Although we could not demonstrate the commutability of human serum pools (commutable EQA), some studies have provided evidence regarding the commutability of these materials through the same preparation technique [ 12 , 14 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 72%
“…After excluding outliers on the basis of three standard deviations, the median values of the NCCL EQA materials were used to determine the systematic biases. The commutability of the EQA materials was carried out following Clinical and Laboratory Standards Institute (CLSI) guideline EP30-A and difference in bias based on the recommendations by the IFCC Working Group on Commutability [12][13][14][15] and commutability-related biases were determined on the basis of backcalculation among assays after correcting for systematic biases via Deming regression.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between μg and IU usually is given as 1.21 μg = 1000 IU, but conversion factors may widely vary by assay and this may represent a significant source of inter-assay variability and bias. Furthermore, the commutability of WHO 72/225 preparation has been questioned [47] and some authors have observed that running immunoassays still suffer from significant inter-method variability limiting the comparability of AFP results [48].…”
Section: The Importance Of the Afp Assaymentioning
confidence: 99%
“…As with other protein biomarkers, in large centralized facilities, the methods of choice for AFP detection are immunoassays performed in automated instruments [7]. To reduce the ever-increasing health expenditures and decentralize the analysis, the extreme success of glucometer for diabetes patients, an electrochemical biosensor, is a model to imitate.…”
Section: Introductionmentioning
confidence: 99%